The Effect of Reading The Novel "Laut Bercerita" by Leila S. Chudori on The Mindset of Grade XII Students in Assessing Indonesian History and Politics Through Literary Works - Sari Mulyani, Iis; Sobari, Teti (JLER (Journal of Language Education Research), 2025)
The current young generation has a low interest in history and politics. History and politics are often considered boring and uninteresting. Apart from that, the rapid development of the times makes history seem to be forgotten and denied. History, in particular, is something that teenagers consider to be just a thing of the past. In fact, the formation of a nation, including Indonesia, of course involves history and politics which have an important role in formulating its existence. There are actually many things that can be done to foster the interest of the younger generation so that they are interested and willing to study history and politics, one of which is through literary works. In fact, history was once part of literature, therefore students' thinking patterns regarding history and politics can develop through learning literary appreciation, namely by reading and analyzing a literary work. Political history, which is part of life, is reviewed in novel form so that it can provide an attraction for readers to study political history indirectly. Reading the novel "Sea Bercerita" by Leila S. Chudori can have an influence on the reader's own mindset regarding interest in contemporary history-politics indirectly both in terms of expanding historical-political knowledge, developing empathy for various perspectives, and stimulating reflection about values of life.